First Seroprevalence Study of Feline Leukemia and Feline Immunodeficiency Infections Among Cats in Algiers (Algeria) and Associated Risk Factors - Fatima Yahiaoui; Moustafa Kardjadj; Meriem Hind Ben-Mahdi (Veterinary Sciences)
Feline leukemia and feline immunodeficiency virus infections are two widespread diseases that affect the health of domestic cats all over the world. In Algeria, despite the existence of a large population of cats, there are no published data regarding the epidemiological status of feline retroviruses. Therefore, the objective of the present study was to estimate the seroprevalence of FIV and FeLV infections in cats in Algiers and to assess the main factors associated with the infection. A cross-sectional study was conducted in which 71 cats were sampled from several private veterinary clinics, and their obtained sera were tested using an immunochromatography analysis (SNAP Duo FIV/FeLV Test; Virbac Laboratories, France). The seroprevalence was about 32.39% and 22.53% for FIV and FeLV, respectively. Overall, 11.26% were positive for both infections. The present study showed that FIV seropositivity was associated with a younger age and health status (p < 0.05), while FeLV seropositivity was associated with the sex, reproductive status, housing, age, and health status of the cats. This preliminary study, which utilized rapid tests, provides important initial data revealing a relatively high prevalence of retroviruses in cats in Algeria. The results underscore the urgent need for implementing both preventive and management measures to control the spread of these retrovirus diseases. However, to enhance the reliability of future findings, it is essential to expand the sample size and incorporate reference diagnostic methods.